2010
DOI: 10.1007/s11090-010-9214-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of C2H4/N2 Ratio in an Atmospheric Pressure Dielectric Barrier Discharge on the Plasma Deposition of Hydrogenated Amorphous Carbon-Nitride Films (a-C:N:H)

Abstract: The goal of this study was to investigate the properties and growth mechanisms of nitrogen-containing carbon-based coatings obtained with an atmospheric pressure dielectric barrier discharge in an N 2 -C 2 H 4 atmosphere. Radically different chemical compositions were observed depending on C 2 H 4 /N 2 ratio. With a low C 2 H 4 concentration (\400 ppm) as a function of the residence time in the discharge, two different growth mechanisms were observed consisting of a highly nitrogenated coating (N/C [ 0.8) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 74 publications
4
10
0
Order By: Relevance
“…Comparison of C 2 H 2 /N 2 and C 2 H 4 /N 2 (left) and of C 2 H 4 /N 2 and C 2 H 6 /N 2 mass spectra with plasma in the mass range M/Z up to 180. Similar ratios had been observed for films deposited in a C 2 H 4 /N 2 dielectric barrier discharge plasma (Sarra-Bournet et al, 2010).…”
Section: Properties Of Deposited Filmssupporting
confidence: 82%
“…Comparison of C 2 H 2 /N 2 and C 2 H 4 /N 2 (left) and of C 2 H 4 /N 2 and C 2 H 6 /N 2 mass spectra with plasma in the mass range M/Z up to 180. Similar ratios had been observed for films deposited in a C 2 H 4 /N 2 dielectric barrier discharge plasma (Sarra-Bournet et al, 2010).…”
Section: Properties Of Deposited Filmssupporting
confidence: 82%
“…These experiments showed that the amount of surface amino groups was 2.5%, corresponding approximately to 0.5-2 amine/nm 2 [42], and was thus adequate for surface conjugation. Another interesting finding is that these data were recorded 1 week after the organic layer deposition, thus confirming that the remaining amine concentration was stable and no longer susceptible to aging effects [43,44].…”
Section: Topography Analyses and Evaluation Of The Mechanical Propertsupporting
confidence: 54%
“…4) generally involves four components (or sub-peaks), here labelled cc, c1, c2 and c3. Several different attributions can be found in the literature, but none appear to be completely satisfactory, on [42]. These assignments, which are mainly deduced from comparisons with chemical shifts in standard polymers [32], cannot be considered reliable for quantitative analyses.…”
Section: Resultsmentioning
confidence: 99%